Relasi Pendidikan Keislaman dan Sikap Moderasi Beragama Peserta Didik: Analisis Regresi Sederhana - Tri Prasetiyo, Nova; syafi'i, Imam; Akhyak, Akhyak; Tanzeh, Ahmad; Rohim, Muhammad (PAI RAFAH, 2025)
This study aims to analyze the relationship between Islamic education and students’ religious moderation attitudes at Madrasah Aliyah Al-Muhajirin Purwakarta using a quantitative approach with simple regression analysis. Religious moderation is a crucial issue in the context of Islamic education as it shapes students to become tolerant, inclusive, and balanced individuals in practicing their faith. The data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The research instrument was tested for validity and reliability to ensure data accuracy. The findings reveal that Islamic education has a positive and significant effect on students’ attitudes of religious moderation, although the contribution level remains limited. These results highlight the importance of strengthening the curriculum and teaching strategies that instill Islamic values of rahmatan lil ‘alamin, while encouraging students to develop moderate attitudes in dealing with diversity. This research is expected to provide theoretical contributions to Islamic education studies and practical implications for policy development in madrasah learning.